Efficacy of cognitive-behavioral therapy for prolonged grief - Sanz Molina, Belén; Sanz Cortés, Ana; Cruzado, Juan Antonio (Psicooncología, 2023)
Background: Prolonged Grief (PG) is a pathological form of bereavement given the overt symptoms and the period of time they endure, generating distress and limiting psychosocial functioning. For years, Cognitive Behavioral-Therapy (CBT) has been used for the treatment of PG. Nonetheless, it is suggested that non-specific behavioral activation could be sufficient, methodological problems are found in CBT samples, or it is questioned whether the exposure component is necessary or not. Objective: To analyze whether CBT is really effective to improve PG among the adult population. Methods: A systematic review was conducted through Medline, PsycINFO, PubMed, Scopus and Web of Science databases from June 2022 to February 2023, as well as by means of personal communication. 9 studies that met the established inclusion and exclusion criteria were identified. Results: Baseline, post-treatment and follow-up assessments are compared. All studies reflect superior improvements in the CBT condition compared to other therapeutic modalities or compared to CBT without exposure, excluding one study that establishes equal efficacy with Eye Movement Desensitization and Reprocessing (EMDR). The risk of bias was analyzed according to Cochrane criteria, presenting an adequate methodological quality; the level of scientific evidence, 1+; and the grade of recommendation, A. Conclusions: The results support the efficacy of CBT for the treatment of PG in the adult population. Nevertheless, it is essential to conduct new studies that strengthen this evidence. Until then, it is recommended its application among those suffering from PG.
Keywords: Prolonged grief; cognitive-behavioral therapy; exposure